2002
DOI: 10.1067/mva.2002.124366
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is involved in the development of experimental abdominal aortic aneurysm: A study of the transcription profile with complementary DNA microarray

Abstract: The cDNA microarray technique was useful for investigation of the transcription profiles during the development of AAA. Our results indicate that oxidative stress may play a pivotal role in the pathologic progression of AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 0 publications
5
62
0
Order By: Relevance
“…12) In addition to activation of proteolysis and inflammation, apoptosis of smooth muscle cells 13) and oxidative stress 14,15) have been suggested by several clinicopathological studies, and these factors together with many others seem to be intricately interwoven to produce aneurysms. Another difficulty is that suitable animal models are not available for the study of aortic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…12) In addition to activation of proteolysis and inflammation, apoptosis of smooth muscle cells 13) and oxidative stress 14,15) have been suggested by several clinicopathological studies, and these factors together with many others seem to be intricately interwoven to produce aneurysms. Another difficulty is that suitable animal models are not available for the study of aortic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in which tissue availability was not a limiting factor have consistently shown a correlation between differential gene expression identified through microarray analysis and realtime PCR. [15][16][17][18][19][20][21][22][23][24][25] Total RNA for real-time PCR analysis was extracted from liver tissue (ϳ5 mg) of subjects with NASH (n ϭ 6) and from 2 groups of control subjects without NASH (cirrhosis secondary to PBC, n ϭ 6), and body mass index, gender-and age-matched subjects with normal liver histology and biochemical profiles (healthy controls, n ϭ 6) by TRIZOL method (Life Technologies). One microgram of total RNA was treated with DNase (Life Technologies) and then reverse transcribed using the TaqMan Reverse Transcription Reagents (PE Biosystems, Foster City, CA) according to the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have demonstrated that proinflammatory cytokines, such as interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ, can enhance inducible nitric oxide synthase (iNOS) expression in vascular smooth muscle cells (SMC), and other cell types such as macrophages [1][2][3]. Oxidative stress has been shown to be associated with aortic aneurysm formation in both human tissue and animal models [4][5][6]. Reactive oxygen species (ROS), including superoxide anion (O 2 − ), hydroxyl radical, and reactive nitrogen species, such as nitric oxide (NO) and peroxynitrite, are increased in human AAA [7], suggesting that ROS are one of the possible contributors to arterial wall degeneration.…”
Section: Introductionmentioning
confidence: 99%